DOI: 10.14264/uql.2017.24
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally-related health impacts of coal seam gas development: An impact assessment approach in Queensland, Australia

Abstract: Queensland, Australia has a large mining industry and has been extracting coal seam gas (CSG) on an increasingly larger scale in recent years. CSG is a type of unconventional natural gas.Historically, concerns associated with unconventional natural gas development (UNGD) have come from areas where types of UNGD other than CSG are predominant. While shale gas and CSG development are not identical, there is an underlying theme of community concern about the potential environmentally-related health impacts (ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 169 publications
(385 reference statements)
0
1
0
Order By: Relevance
“…A previous ecological study compared all-age hospitalisation rates in the same CSG study area used here to coal mining and rural/agricultural study areas and found that hospitalisation rates for “Blood/immune” diseases, “Neoplasms”, and “Congenital” outcomes increased in the CSG study area relative to the hospitalisation rates in the other study areas [ 19 , 37 ]. Additionally, age-specific studies found increasing “Blood/immune” disease admission rates in a CSG study area compared to the other study areas and decreasing rates for one child/adolescent age group [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous ecological study compared all-age hospitalisation rates in the same CSG study area used here to coal mining and rural/agricultural study areas and found that hospitalisation rates for “Blood/immune” diseases, “Neoplasms”, and “Congenital” outcomes increased in the CSG study area relative to the hospitalisation rates in the other study areas [ 19 , 37 ]. Additionally, age-specific studies found increasing “Blood/immune” disease admission rates in a CSG study area compared to the other study areas and decreasing rates for one child/adolescent age group [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%